Design, analysis and fabrication of Malay traditional snacks cutter / Amirah Hanis Azman - Azman, Amirah Hanis (2022)
Malay Traditional Snacks Cutter is a new generation of the best solution any snack sellers can ever ask for. If you were walking at markets, be it a night market or a morning market, there will definitely be at least one hawker who sells Malay traditional snacks such as kuih talam, kuih lapis, kuih seri muka and kuih kaswi. This innovation, with simple controls and operations, can simply reduce the cutting process duration, produce more accurate size of each piece of snack and make the cutting process tidier. Most part of the product is made out of aluminum sheet metals. Hence, welding, drilling and milling will be involved during fabrication process. Compared to the conventional methods, this innovation will be a big of help for snack sellers in order to reduce their time and to produce a better quality of snacks for their customers.